Synthetic Cannabinoid Agonist WIN 55212-2 Targets Proliferation, Angiogenesis, and Apoptosis via MAPK/AKT Signaling in Human Endometriotic Cell Lines and a Murine Model of Endometriosis - Lingegowda, Harshavardhan; Miller, Jessica E.; Marks, Ryan M.; Symons, Lindsey K.; Alward, Taylor; Lomax, Alan E.; Koti, Madhuri; Tayade, Chandrakant (Frontiers in Reproductive Health, 2021)
Endometriosis (EM) is characterized by growth of endometrium like tissue outside the uterus, leading to chronic inflammation and pelvic pain. Lesion proliferation, vascularization and associated inflammation are hallmark features of EM lesions. Legalization of recreational cannabinoids has garnered interest in patient community and is contributing to greater incidence of self medication, however, it remains unknown if cannabinoids possess marked disease modifying properties. Here we assess the effects of synthetic cannabinoid, WIN 55212-2 (WIN 55) in EM representative in vitro and in vivo syngeneic mouse models. WIN 55 reduced proliferation and angiogenesis in vitro, via MAPK/Akt-mediated apoptosis. These findings were corroborated in a mouse model of EM, where we found reduced TRPV1 expression in the dorsal root ganglia of EM mouse model exposed to WIN 55, suggesting reduced signaling of pain stimuli. Ultimately, these evidences support the use of cannabinoid receptor agonists as a potential therapeutic intervention for EM associated pain and inflammation.